Proposal of point-wise power reconstruction for IRT-4M fuel assemblies in coupled Monte-Carlo calculations - Pavel Jíška; Jan Frýbort (Acta Polytechnica CTU Proceedings)
Current efforts to develop high-fidelity multi-physics tools for research reactors with IRT-4M fuel leads to the involvement of Monte-Carlo transport and subchannel thermo-hydraulic codes in the process of safety assessment. Monte-Carlo based neutronic codes are often used as a reference tool and are suitable for a prediction of a detailed power distribution. This paper proposes a method of the point-wise power reconstruction based on a Radial Basis Function (RBF) interpolation for complicated irregular geometries and compares different detector functionalities of the Serpent2 code from the time efficiency point of view. Furthermore, a preliminary validation of the applied method for IRT-4M in a subchannel code SUBSALS mesh is presented. This code is currently under the  evelopment at the Research Centre Rež and the Czech Technical University in Prague and focuses on the thermohydraulic analysis of IRT type fuel assemblies.